TRADISI MEGANTUNG ARI-ARI (PLACENTA) DI DESA ADAT PEKRAMAN TRUNYAN KINTAMANI BANGLI - Yasa, I Nyoman Kartika (LPPM IKIP PGRI Bali, 2019)
In general, the community maintains the placenta after the mother gives birth to the baby in the front door of the house, Namu to the Pekraman Trunyan traditional village community after the mother gives birth to the baby, Ari-ari (Placenta) is hung on a wooden tree branch in one of the Tantanbuni places .         The theory used to dissect the problem The unique tradition of hanging Ari-ari (placenta) is the Sociological Theory of Herbert Spencer with the functional Structural Theory and the Principle Theory of Religion by Kuentjaraningrat. Data were collected by observation, interview and document documents.         Based on the results of the study revealed that, the background factors in the beliefs and beliefs of the people of Trunyan Village were received from their ancestors since the descent